Factor structure and psychometric properties of a Persian translation of the Epworth Sleepiness Scale for Children and Adolescents - Vida Imani; Chung-Ying Lin; Shabnam Jalilolgadr; Amir H. Pakpour (Tabriz University of Medical Sciences, 2018)
Background: Given the high prevalence of excessive daytime disorder (EDS) among children and adolescents, daytime sleepiness should be effectively measured for them to design appropriate intervention program. However, the commonly used instrument Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) has little information in its psychometric properties. This study aimed to apply 2 different test theories to examine the psychometric properties of the Persian ESS-CHAD among a large sample of Iranian adolescents and children.Methods: In this methodological study, participants from 8 high schools (n=1371; 700 males), in Qazvin, Iran, completed the ESS-CHAD, a background information sheet, and Insomnia Severity Index (ISI). The ESS-CHAD was translated by using a forward-backward translation method.Two weeks later, the participants completed the ESS-CHAD again. Internal consistency using Cronbach's alpha, test-retest reliability using intraclass correlation coefficient (ICC), regression analysis testing the correlation between ESS-CHAD and ISI, Confirmatory factor analysis (CFA)with measurement invariance, Rasch analysis with differential item functioning (DIF), and latent class analysis (LCA) were used to examine the psychometric properties of the ESS-CHAD. Results: The internal consistency (α=0.79), test-retest reliability (ICC=0.84), regression findings(β=0.39, P<0.001), CFA (comparative fit index [CFI])=0.974, root-mean square error of approximation [RMSEA]=0.040), supported measurement invariance (∆CFI=-0.009 to 0.007,∆RMSEA=-0.009 to 0.001), Rasch analysis (infit mean square=0.88 to 1.31, outfit mean square=0.68 to 1.19), and no substantial DIF (DIF contrast=-0.43 to 0.38) all indicated that ESSCHAD is a reliable and valid instrument. The LCA further classified the sample into 2 distinctclasses. Conclusion: Persian ESS-CHAD could be used to assess daytime sleepiness for adolescents whoare speaking Persian.